1995
DOI: 10.1111/j.1532-5415.1995.tb07400.x
|View full text |Cite
|
Sign up to set email alerts
|

SPECT in Dementia: Clinical and Pathological Correlation

Abstract: SPECT provides useful positive information in dementia, particularly the differentiation of AD, FTD, and JCD. However, it does not distinguish PD from AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
0
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 100 publications
(52 citation statements)
references
References 33 publications
3
48
0
1
Order By: Relevance
“…SPECT and PET may be helpful in distinguishing FTD from AD. Many patients with FTD show hypoperfusion of anterior cerebral cortex with relative sparing of posterior cortex with SPECT [78][79][80] and PET. 81 In these four Class II studies, the highly selected study participant pool makes it difficult to generalize on the reported specificities and sensitivities.…”
mentioning
confidence: 99%
“…SPECT and PET may be helpful in distinguishing FTD from AD. Many patients with FTD show hypoperfusion of anterior cerebral cortex with relative sparing of posterior cortex with SPECT [78][79][80] and PET. 81 In these four Class II studies, the highly selected study participant pool makes it difficult to generalize on the reported specificities and sensitivities.…”
mentioning
confidence: 99%
“…The changes in frontal and in temporal blood flow grow more marked as the disease progresses [43][44][45] providing information for diagnosing it in 90% of cases, especially if they are correlated with clinical parameters. 46 Therefore, there were also some difficulties posed by the neuroimaging and neuropsychological examinations described in the studies which also precluded the combined evaluation of data.…”
Section: Discussionmentioning
confidence: 99%
“…Studies with no direct comparison found sensitivity of 93% and specificity of 74% using SPECT (Read et al, 1995), and 96% and 89% (Jobst et al, 1994). Initial regional cerebral blood flow SPECT studies of MCI may be useful in predicting patients who will develop AD in the near future (Hirao et al, 2005).…”
Section: Comparison With Mr Imaging Single Photon Emission Computed mentioning
confidence: 99%